Pengabdian Kepada Masyarakat (PKM) Pemberian Umbi Talas Untuk Mengontrol Kadar Glukosa Darah di Wilayah Kampung Sidomulyo Distrik Semangga - Ahmad Hanafi; Asyabillah P. Ramadhani; Siti Khoyriyah; Frety Shinta; Eunike A. Laga; Laili Nur Hidayati (Jurnal Pengabdian Bidang Kesehatan, 2025)
Diabetes mellitus (DM) is one of the groups of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin function or both. DM is caused by lifestyle changes and lack of awareness to detect DM early, lack of physical activity, and poor diet. The dominant lifestyle that triggers DM is diet and physical activity. Changes in lifestyle such as unhealthy food habits and lack of physical activity have a high risk of developing diabetes. Implementation of community service activities through counseling using leaflets and posters. The next activity is to provide taro tubers to sufferers with the aim of controlling blood glucose levels. The outputs used in this community service activity include publications and videos of activities conveying the benefits of taro tubers to control blood glucose levels.